Analisis Keamanan Jaringan Pada Jaringan Wireless Dari Serangan Man In The Middle Attack DNS Spoofing - Teguh Pangestu; Risko Liza (JITEKH, 2022)
Currently the use of wireless technology (wireless) is widely used in institutions, companies, schools and so on. Wireless is very useful because it can facilitate human interaction activities in sending data and so on. However, the existence of wireless is not completely safe in carrying out human interaction activities in sending data and so on, one of which is the illegal man in the middle attack DNS spoofing activity. With these illegal activities, a security system is needed which is expected to prevent illegal man in the middle attack DNS spoofing activities. The results of the attack are obtained based on 7 tests by calculating the quality of service (QOS), namely packet loss with the results of attack 1 model 1 with packet loss 0.154%, attack 2 model 1 with packet loss 0.234%, attack 3 model 1 with packet loss 0.291%, attack 1 model 2 with packet loss 0.173%, attack 2 model 2 with packet loss 0.128%, attack 3 model 2 with packet loss 0.028%, attack 4 model 2 with packet loss 0.231%, which means this attack can run well. And the results by utilizing a firewall security system can only prevent it by cutting off communication interactions between the attacker and the victim and the victim and the attacker.